(untitled) (Research, Society and Development, 2022)
This article known the Biology teachers perceptions in relation to genetics as a whole and specifically to the ABO System content, as well as enabling a didactic tool to better work on this content in the classroom. The contact with the teachers occurred through free messaging application (WhatsApp). Research participants electronically signed the Free and Informed Consent Form and filled out a semi-structured online form (via Google Forms), made available through the WhatsApp application. The work in question also proposed to build a didactic model related to the ABO system, with the objective of facilitating the process of teaching and learning this content. Twenty-six teachers responded to the survey, and in the responses, it was observed that, for the majority, the content of genetics was worked inappropriately and did not contribute much to their training during graduation. Additionally, they stated that the greatest difficulty in genetics refers to the calculations used in the discipline. Regarding the ABO system, most teachers like to teach the content, but they experience difficulty due to the lack of didactic materials to optimize the teaching of the content in question. Finally, most teachers approved the didactic model made during the research and declared interest in using this model, stating that it contributes to the teaching-learning process of students. From this, it is concluded that, although teachers like the content, there are difficulties in the teaching-learning process of the ABO system, in addition to the use of other methods for teaching genetics.